LAJU FILTRASI GLOMERULUS PASIEN DIABETES MELITUS TIPE II DI SALAH SATU RUMAH SAKIT SWASTA DI KABUPATEN DEMAK - Rukminingsih, Fef; Widiastuti, Mei (Jurnal Riset Kefarmasian Indonesia, 2021)
Diabetes Mellitus (DM) Type II is a group of metabolic diseases with hyperglycemia characteristics. The use of oral hypoglycemic drugs (OHO) lasts for a relatively long time. Most of the OHO is excreted through the kidneys. This study aims to determine the Glomerulus Filtration Rate (GFR) of type 2 DM patients who use OHO at the "X" Hospital, District of Demak. This study is an observational descriptive study using retrospective data obtained from medical record data (RM) of outpatient JKN participants with type 2 DM for the period October-December 2020. Inclusion criteria were patients who received OHO for at least one year with or without comorbidities, aged 36-65 years, and had a serum creatinine test. Patients receiving combination therapy with insulin were excluded. LFG is calculated using the Cockroft-Gault formula. From 82 patients, 52 patients (62.2%) were female, 74 patients (90.2%) were more than 45 years old. Patients who consumed OHO for more than 2 years were 47 (57.3%). Patients without comorbidities were 62 (75.7%) people. Patients who experienced a decrease in GFR in the moderate category (stage 3) as many as 24 people (29.3%), a decrease in GFR in the severe category (stage 4) as many as 5 people (6.1%) and 1 person (1.2%) experienced End Stage Renal Disease.